2018
DOI: 10.21037/apm.2017.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for patients with advanced neurology diseases

Abstract: EOL decision making in patients with advanced neurology disease is often delayed. This study showed that MND patients are readier to discuss their EOL issues and signed their AD. The NPCT can play a valuable role in EOL discussions in patients with advanced neurology diseases under collaboration between the PC and the neurology teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…In a retrospective chart review, Cheung et al (2017) [ 83 ] investigated the EOL care communication, preferences and documentation among patients with end-stage neurological disorders (stroke, myopathies, motor neuron disease, MS, parkinsonism). Results showed that most patients would decide for EOL issues during their first consultations.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective chart review, Cheung et al (2017) [ 83 ] investigated the EOL care communication, preferences and documentation among patients with end-stage neurological disorders (stroke, myopathies, motor neuron disease, MS, parkinsonism). Results showed that most patients would decide for EOL issues during their first consultations.…”
Section: Resultsmentioning
confidence: 99%
“…44 , 90 Therefore, 16 publications mention different tools for ACP offered to PALS (including ADs or other documents, such as a preferred priorities for care document, end-of-life care plan or letter for future care). 14 , 42 , 60 , 61 , 64 , 70 , 73 , 78 , 87 , 93 , 107 , 109 , 110 , 121 123 However, the guidance to conclude such a document is sometimes more 61 , 87 , 103 , 115 and sometimes less sufficient. 47 Prevalence rates for completed documents vary according to the time of data collection and national context.…”
Section: Resultsmentioning
confidence: 99%
“…All patients in the ACP had do-not-attemptcardiopulmonary-resuscitation (DNACPR) order. Mean age (SD) of ACP group and non-ACP groups were 58.8 [13] and 60.4 [16] years old respectively, and approximately 46-47% were men in both groups. The median of the number of sessions to achieve ACP was 4.3 (range, 2-7 sessions).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Due to the socio-cultural differences, the implementation of ACP remains difficult in the EOL care for local Chinese patients with advanced medical illness (12,13). In this context, there is social taboo to discuss ACP in elderly Chinese patients.…”
Section: Introductionmentioning
confidence: 99%